Overexpression of Bone Morphogenetic Protein-1 Promotes Osteogenesis of Bone Marrow Mesenchymal Stem Cells In Vitro - Su, Zhongping (Med Sci Monit, 2020)
BACKGROUND: Osteogenesis of bone marrow mesenchymal stem cells (BMSCs) is an important research topic in the application of bone tissue engineering. Bone morphogenetic protein-1 (BMP-1) is important in bone formation and stability, but its effects on the osteogenesis of BMSCs are unclear. This study aimed to investigate the association of BMP-1 with the osteogenic capacity of BMSCs. MATERIAL/METHODS: Primary rabbit BMSCs were cultured and divided into a BMP-1-overexpressing group, a Green Fluorescent Protein-expressing (GFP) group, and a Control group. The transfection efficiency of BMP-1 was tested by Western blotting. Cell viabilities, alkaline phosphatase (ALP) activities, Ca(2+) concentrations, and gross examinations of BMSC sheets were examined at different times. The osteogenic marker collagen I was assessed by immunohistochemical analysis. RESULTS: The cell viability, ALP activity, and Ca(2+) content of the BMP1-overexpressed group were significantly enhanced compared with the GFP group and Control group. Immunohistochemistry staining results showed that BMP-1 promoted the expression of type I collagen in BMSCs sheets. CONCLUSIONS: Our results suggest that the overexpression of BMP-1 can promote the osteogenesis of BMSCs and provides an improved method of cell-based tissue engineering.